2016
DOI: 10.1136/bmjopen-2016-012090
|View full text |Cite
|
Sign up to set email alerts
|

Gender equity programmes in academic medicine: a realist evaluation approach to Athena SWAN processes

Abstract: ObjectivesGender inequity has persisted in academic medicine. Yet equity is vital for countries to achieve their full potential in terms of translational research and patient benefit. This study sought to understand how the gender equity programme, Athena SWAN, can be enabled and constrained by interactions between the programme and the context it is implemented into, and whether these interactions might produce unintended consequences.DesignMultimethod qualitative case studies using a realist evaluation appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
143
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(151 citation statements)
references
References 26 publications
7
143
0
1
Order By: Relevance
“…27 Our results also align with findings from a systematic review of interventions that mitigate gender bias in employment, which found bias against women being evaluated for positions that are traditionally or predominantly held by men. 28 This review identified strategies to mitigate this bias, including aiming for an applicant pool with at least 25% women, committing to the value of credentials before applicants are reviewed and training panel members in unconscious bias and the role that it can play in discussions and decisions.…”
Section: Discussionsupporting
confidence: 78%
“…27 Our results also align with findings from a systematic review of interventions that mitigate gender bias in employment, which found bias against women being evaluated for positions that are traditionally or predominantly held by men. 28 This review identified strategies to mitigate this bias, including aiming for an applicant pool with at least 25% women, committing to the value of credentials before applicants are reviewed and training panel members in unconscious bias and the role that it can play in discussions and decisions.…”
Section: Discussionsupporting
confidence: 78%
“…Recent data from a realist evaluation show that the Athena SWAN program is perceived to have an important impact across participating universities but is associated with a heavy workload to fulfil its requirements. Further complicating this issue is that the workload is largely being shouldered by women, unintentionally reproducing gender inequity through its very enactment [53]. Establishing best practices for grant peer review to reduce gender bias will benefit from more supporting evidence.…”
Section: Resultsmentioning
confidence: 99%
“…The Athena SWAN framework, introduced in the United Kingdom in 2005, aimed to address underrepresentation of women within STEMM careers through an awards scheme that promoted structural and cultural change within the higher education and research sector . The introduction of the program was associated with an increase in female representation in academic medicine posts . The program has been piloted in Australia as The Science in Australia Gender Equity (SAGE) initiative and has been adopted by over 50% of Australian academic institutes…”
Section: Discussionmentioning
confidence: 99%
“…23 The introduction of the program was associated with an increase in female representation in academic medicine posts. 26 The program has been piloted in Australia as The Science in Australia Gender Equity (SAGE) initiative and has been adopted by over 50% of Australian academic institutes. 23 Almost half of all respondents reported experiencing DBSH with female ophthalmologists nearly four times more likely to report discrimination and 50 times more likely to report sexual harassment compared to their male counterparts.…”
Section: Discussionmentioning
confidence: 99%